Q: Find the ordered pair solution to the following system of equations (Use any method):
3x – 2y = –1
2x + y = 4
(Points : 5)
(2, 1)
(1, 2)
(1, 1)
(2, 2)

A: The answer is (1, 2) {3x+1=2y,2x+y=4} {y=3x/2+1/2,y=4-2x} x=1 , y=2

Expert answered|wiwit|Points 630|

Question

Asked 8/21/2012 8:16:14 PM

Updated 8/25/2012 11:50:26 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by jeifunk

Rating

3

The answer is (1, 2)

{3x+1=2y,2x+y=4}

{y=3x/2+1/2,y=4-2x}

x=1 , y=2

{3x+1=2y,2x+y=4}

{y=3x/2+1/2,y=4-2x}

x=1 , y=2

Added 8/25/2012 11:50:26 AM

This answer has been added to the Weegy Knowledgebase

. Which ordered pair below has an x-coordinate value of 3, and a y-coordinate value of –2? (Points : 5)

Question

Expert Answered

Updated 2/13/2015 3:42:17 AM

1 Answer/Comment

Given the function f(x) = - 2x , find the value of f(–1). **Weegy:** f(-1) = (-1)^2 - 2(-1) = 3
f(1) = 1^2 - 2(1) = -1 (More)

Question

Expert Answered

Updated 9/16/2014 12:52:57 AM

1 Answer/Comment

When f(x) = - 2x , the value of f(–1) is 2.

f(-1) = -2*(-1) = 2.

f(-1) = -2*(-1) = 2.

Added 9/16/2014 12:47:39 AM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by andrewpallarca [9/16/2014 12:52:53 AM], Rated good by andrewpallarca

What is the slope m and y-intercept point of the line y = 2x + 1?

Question

Expert Answered

Updated 67 days ago|2/17/2017 11:22:26 PM

1 Answer/Comment

In the form, y = mx + b, m stands for the slope and b stands for the y-intercept; therefore, in the equation y = 2x + 1,

Slope: 2

y-intercept: 1

Slope: 2

y-intercept: 1

Added 67 days ago|2/17/2017 11:22:26 PM

This answer has been confirmed as correct, not copied, and helpful.

If the system of equations given below is solved using the substitution method, what is the equation that results from solving the second equation for y, and substituting into the first equation?
3x - 2y = 7
x - y = 5
**Weegy:** (3x-2) squared is 9x^2 - 12x + 4. (More)

Question

Expert Answered

Updated 5/3/2015 8:52:26 AM

1 Answer/Comment

3x - 2y = 7 (equ. 1)

x - y = 5 rearranging the equation we get:

y = x - 5 (equ. 2)

using equation 2 to substitute y in the equation 1 the result is

3x - 2(x - 5) = 7

the equation that results from solving the second equation for y, and substituting into the first equation is 3x - 2(x - 5) = 7

x - y = 5 rearranging the equation we get:

y = x - 5 (equ. 2)

using equation 2 to substitute y in the equation 1 the result is

3x - 2(x - 5) = 7

the equation that results from solving the second equation for y, and substituting into the first equation is 3x - 2(x - 5) = 7

Added 5/3/2015 8:52:24 AM

This answer has been added to the Weegy Knowledgebase

If the system of equations given below is solved using the substitution method, what is the equation that results from solving the second equation for y, and substituting into the first equation?
3x - 2y = 7
and
x - y = 5
**Weegy:** (3x-2) squared is 9x^2 - 12x + 4. **User:** If the system of equations given below is solved using the substitution method, what is the equation that results from solving the second equation for y, and substituting into the first equation?
3x - 2y = 7 and
x - y = 5
(More)

Question

Expert Answered

Updated 7/7/2014 11:53:35 PM

1 Answer/Comment

3x - 2y = 7 and x - y = 5, The equation that results from solving the second equation for y, and substituting into the first equation is: 3x - 2x + 10 = 7.

3x - 2y = 7 (equation 1)

x - y = 5 rearranging the equation we get: y = x - 5 (equation 2)

using equation 2 to substitute y in the equation 1:

3x - 2(x - 5) = 7

or 3x - 2x + 10 = 7

3x - 2y = 7 (equation 1)

x - y = 5 rearranging the equation we get: y = x - 5 (equation 2)

using equation 2 to substitute y in the equation 1:

3x - 2(x - 5) = 7

or 3x - 2x + 10 = 7

Added 7/7/2014 11:53:28 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by jeifunk [7/7/2014 11:54:05 PM]

27,390,548 questions answered

There are no comments.